The Application of DNA Molecular Marker Techniques in Hevea Brasiliensis - Atan, Safiah (2001)
DNA was extracted from several Hevea sources; namely, various Hevea species, several cultivars from within the Hevea brasiliensis species such as clones and in vitro cultured H. brasiliensis. Four DNA molecular marker techniques were used to analyze the DNA. These techniques included a hybridization-based marker technique called restriction fragment length polymorphism (RFLP) and three polymerase chain reaction (PCR)-based techniques viz. random amplified polymorphic DNA (RAPD), DNA amplified fingerprinting (DAF) and sequence-tagged microsatellite sites (STMS). In the RFLP study, a wheat ribosomal DNA, pTa71 (rDNA) probe was able to detect a reduction in rDNA loci number in DNA from in vitro cultured plants compared to DNA from control plants. Hybridization with M13 DNA fragments revealed interand intraspecific variations among the DNA samples. Neither of thesehybridization probes could detect somac1onal variation within a sample of in vitro cultured plants. On the other hand, RAPD and DAF were able to detect somaclonal variation within the in vitro cultured plants. The polymorphic patterns produced by RAPD could be neither correlated with any particular morphological trait nor the source of calli i.e. anther or ovule. Meanwhile, DAF proved to be more sensitive as it was able to detect a high degree of variation in the DNA extracted from anther derived calli. STMS could not detect any variation nor insertion/deletion mutation at the HMGR-l gene within the in vitro culture DNA. RAPD and DAF molecular markers were found to be dominant while RFLP and STMS markers were co-dominant in all of the H brasiliensis crosses tested in this study. No change in the methylation sites for both in vitro culture and control plants were detected when the DNAs were digested with both isoschizomeric restriction enzymes Hpall and MspI. A micro satellite enriched library was constructed and was found to be enriched with (GA)n repeats (39%). Hybridization with one of these clones revealed inter- and intraspecific variations with DpnII -restricted DNAs. This clone was subsequently sequenced and found to be an imperfect repeat.